ANALISIS BIBLIOMETRIK: TREN PENELITIAN GREEN ACCOUNTING MENGGUNAKAN SCOPUS DATABASE [BIBLIOMETRIC ANALYSIS: GREEN ACCOUNTING RESEARCH TRENDS USING SCOPUS DATABASE] - Wahyuni, Endah Sri (Perkumpulan Ahli Bimbingan dan Konseling Islam Indonesia, 2024)
This research aims to research trends in green accounting on the Scopus database using VOSViewer. This research uses bibliometric analysis methods. Publications related to green accounting taken from the Scopus database were analyzed using descriptive bibliometric analysis. Data obtained from the Scopus database is saved in CSV and RIS form, then entered and analyzed using VOSViewer. The findings from this research are that research on green accounting has been detected since 1992 and 2024 will be the peak of green accounting research with a total of 34 documents. Green accounting research is dominated by authors from the United States who are affiliated with McGill University. After carrying out a bibliometric analysis with the help of VOSViewer, there are seven clusters in green accounting research.